HEALTH RISK ANALYSIS OF LEAD LEVELS (Pb) IN GREEN LEAFY VEGETABLES FROM TRADITIONAL MARKETS AND SUPERMARKET IN SEMARANG CITY: A PRELIMINARY STUDY - Puteri Inandin Nabiha; Ririn Arminsih Wulandari (Jurnal Riset Kesehatan, 2020)
Samples of Green Spinach (Amaranthus gangeticus) Kale or Water Spinach (Ipomoea aquatica) and Green Mustards (Brassica rapa I. Subsp. Perviridis Bayley) were collected from three traditional markets and one supermarket in Semarang City, Central Java. The purpose of this descriptive study was to assess lead (Pb) contamination on raw and boiled vegetables and the health risks for residents in Semarang. The Pb of the samples was measured using atomic absorption spectrophotometer (AAS). The result showed Pb in all samples exceeded the standard values from WHO/FAO (0,3mg/kg), Indonesian National Standard (SNI) limit for Heavy Metals on Food (0,5 mg/kg) and The National Agency of Drug and Food Control of the Republic of Indonesia (BPOM) (0,2 mg/kg). The highest accumulation of Pb found in kale from ‘B’ Traditional Market with 6,123 mg/kg and the lowest was kale from supermarket 0,25 mg/kg. The boiling process for vegetables may increase the Pb concentration, considering the cookware materials. Results revealed that there is no risk of potential health problems for residents in the city with current Pb concentration.